Analysis of comparative results in the learning of Programming in Systems Engineering from three models of group work (2019)
The target of this research is to find judge elements, using experiments in the classroom, where teachers could know the excellence model to conform effective teamworks for learning computer programming in the first programming course in Systems Engineering. To reach that we worked during 6 semesters and using three models: 4Q model, talent model and random model. We used observation, interaction, and dialogue, qualitative and quantitative results to find the target of this research project. The results show characteristics in the interactions inside the different models of groups. We concluded that it is possible to find an excellence model of teamwork depending on the specific course in computer programming.